Intrapleural fibrinolytic therapy: How low can we get? - Imran Bin Mohamed Noor; Sze Khen Tan (Annals, Academy of Medicine, Singapore)
Pleural infection is a common medical problem with significant mortality and morbidity.1 Despite advances in antibiotic therapy, the incidence of pleural infection is increasing in the Western world. The management of complicated pleural infections usually involves drainage of pleural effusion from the infected pleural cavity, typically with a pleural drain. When drainage fails, surgery is often required, but is contraindicated in patients who have significant medical comorbidities.